2015
DOI: 10.1111/jopy.12234
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Motivated Agent Through Time: Personal Goal Development During the Adult Life Span

Abstract: This research examined the rank-order and mean-level consistency of personal goals at two periods in the adult life span. Personal goal continuity was considered among a group of young adults (N = 145) who reported their goals three times over a 3-year period and among a group of midlife adults (N = 163) who specified their goals annually over a 4-year period. Goals were coded for a series of motive-based (viz., achievement, affiliation, intimacy, power) and domain-based (viz., finance, generativity, health, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Speaking to the content of personal goals itself, Dunlop et al (2017) recently introduced a typology of motivational dimensions that reflect both the classic implicit motive-based categories (e.g., intimacy, power) and the more content-oriented or domain-based categories frequently considered in recent research (e.g., generativity, health-based goals; see Table 1). The distinction between these two types of content categories is predicated by the fact that, in the case of the former, “the person is not explicitly describing him or herself as having the motive[s]” (McClelland, Koestner, & Weinberger, 1989, p. 691), whereas, in the case of the latter, the motivated agent is aware that his or her goals apply to specific domains.…”
Section: Person Perception: From Traits To Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Speaking to the content of personal goals itself, Dunlop et al (2017) recently introduced a typology of motivational dimensions that reflect both the classic implicit motive-based categories (e.g., intimacy, power) and the more content-oriented or domain-based categories frequently considered in recent research (e.g., generativity, health-based goals; see Table 1). The distinction between these two types of content categories is predicated by the fact that, in the case of the former, “the person is not explicitly describing him or herself as having the motive[s]” (McClelland, Koestner, & Weinberger, 1989, p. 691), whereas, in the case of the latter, the motivated agent is aware that his or her goals apply to specific domains.…”
Section: Person Perception: From Traits To Goalsmentioning
confidence: 99%
“… Note. The second column of this table is adapted from “Studying the Motivated Agent Through Time: Personal Goal Development During the Adult Lifespan” by W. L. Dunlop, B. L. Bannon, and D. P. McAdams, 2017, Journal of Personality .…”
Section: Person Perception: From Traits To Goalsmentioning
confidence: 99%
“…Most often, narrative identity is measured via the administration of a series of prompts for specific key autobiographical scenes, such as life high points, low points, and turning points (see Adler et al, 2017). Once collected, both goals and narratives are then quantified via any number of nomothetic categories (see Adler et al, 2017;Dunlop, Bannon, & McAdams, 2017).…”
Section: Contextualized Personalit Y Beyond Traitsmentioning
confidence: 99%
“…While recognizing that individuals can and frequently do rely on narrative processing for the aforementioned purpose, Dunlop (2015Dunlop ( , 2017Dunlop, Hanley, & McCoy, in press;Dunlop, Harake, Gray, Hanley, & McCoy, 2018;Dunlop et al, 2013;Dunlop, Walker, & Wiens, 2014) recently proposed that narrative processing may be equally useful when individuals work to construct a coherent sense of self within, rather than across, contexts. From this vantage, it becomes sensible to consider the various contextualized narrative identities individuals have crafted to understand themselves as manifest within the recurrent roles (e.g., "my life story as a student"; Dunlop et al, 2013;Dunlop et al, 2014) and domains (e.g., "my life story within the romantic domain"; Dunlop et al, 2017;Dunlop et al, 2018) relevant to their lives.…”
Section: Dunlop and Hanleymentioning
confidence: 99%
“…While varied by specific labels and research procedures, studies have identified similar clusters of human goals such as basic psychological needs of competence, relatedness, and autonomy (Deci and Ryan 2000); core motives of belonging, understanding, controlling, enhancing self, and trusting (Fiske 2014); and fundamental social motive of self-protection, disease avoidance, affiliation, status, mate seeking, mate retention, and kin care (Neel et al 2016). Research has also shown that individual differences in pursuing different kinds of goals such as these tend to be consistent over time (Dunlop et al 2015;Roberts et al 2004), and that the different kinds of goals are related to the Big Five factors of personality traits in systematic ways (Reisz et al 2013;Roberts and Robins 2000).…”
Section: Basic Kinds Of Goalsmentioning
confidence: 99%